(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
Has conducted research on formulation and stability of sunscreen cream onion bulb extract dayak ( Eleutherine Americana L. Merr . ) . From the empirical data for the onions dayak has been used as an anti- cancer prevention and treatment by people of Borneo so it needs to be further investigated to obtain the data laboratory to support the empirical data . Several classes of secondary metabolites found in the bulbs of onions dayak alkaloids , glycosides , flavonoids , phenolics , steroids and tannins . The study was conducted as the basis for the formulation of sunscreen preparations aimed at the prevention of skin cancer . The study was conducted with bulb onions dayak extraction using Soxhlet method with solvent n - hexane , ethyl acetate , n - butanol , and ethanol as the active ingredient of the formula of making preparations . Tests conducted on formulations A and B with the concentration of garlic bulb extract dayak by 0.1% , consisting of physical stability test ( organoleptic , homogeneity ) and chemical ( pH and dosage ) in order to obtain a stable dosage formula . The test results obtained on the organoleptic test was no change in the observations made on each preparation before and after storage at room temperature on day - 7 , -14 , and -21 . Then the homogeneity test of the hedonic test results at 95% confidence level ( SNI 01-2346-2006 ) , concluded that the homogeneity of the preparation in all formulas produced in the category of smooth . Further testing on the pH stability and pH 5.5 to 8.0 to be produced that Formula A and Formula B to pH 7.0 to 7.7 with various concentrations of the extract , after 21 days of storage , inferred pH remains stable and safe dosage for used ( SNI 16-4399-1996 ) as formula sunscreen preparations made from onion bulb extract dayak .